Comparison of Long-Term Use of Low Dose Rituximab and Mycophenolate Mofetil in Chinese Patients With Neuromyelitis Optica Spectrum Disorder - Lin, Jie; Xue, Binbin; Li, Jia; Zhu, Ruofan; Pan, Juyuan; Chen, Zhibo; Zhang, Xu; Li, Xiang; Xia, Junhui (Frontiers in Neurology, 2022)
Background: Several studies have reported the efficacy and safety of rituximab (RTX) and mycophenolate mofetil (MMF) in neuromyelitis optica spectrum disorder (NMOSD). This study aimed to evaluate the efficacy and safety of long-term use of low-dose RTX and MMF in Chinese patients with NMOSD. Methods: We retrospectively reviewed data from patients with NMOSD in our hospital. The enrolled patients were administrated different immunosuppressive agents. We accessed annual relapse rate (ARR), neurological disability (Expanded Disability Status Scale, EDSS), time to the next relapse, and adverse events. Results: EDSS and ARR were both reduced after RTX and MMF treatment. Kaplan-Meier analysis indicated that patients treated with RTX had a longer time to next relapse compared other immunosuppressive agents before RTX (log-rank test: p<0.001). Furthermore, we evaluated the change of EDSS and ARR in RTX and MMF, and patients treated with RTX showed a better reduction. Eleven relapses from seven patients in group RTX and 20 relapses from 14 patients in group MMF were reported during follow-up. Conclusion: Long-term using of low dose of RTX and MMF were effective and tolerable in Chinese patients with NMOSD, and RTX was more effective than MMF.